Comprehensive Monitoring of Psychoactive Substances in Psychiatric Patients Using Liquid Chromatography-High-Resolution Mass Spectrometry: A Key Tool for Treatment Planning and Understanding Consumption Patterns in Rome, Italy - La Maida, Nunzia; Di Giorgi, Alessandro; Pichini, Simona; Pellegrini, Manuela; Di Trana, Annagiulia; Elmo, Maria Giuseppa; Polselli, Gian Marco; Casella, Pietro; Di Stefano, Adele; Ducci, Giuseppe (Therapeutic drug monitoring, 2024)
The comprehensive monitoring of licit and illicit drug consumption plays a crucial role in understanding the complexities of patient conditions and designing effective treatment strategies. In this study, the prevalence of psychoactive prescription drugs, classical illicit drugs, and new psychoactive substances (NPS) were objectively assessed in individuals diagnosed with drug-related psychiatric disorders or episodes. Blood, urine, and hair samples were collected from psychiatric patients admitted to the Mental Health Department and Drug Addiction Service of the North Rome Local Health Authority with declared or suspected psychoactive drug use. Comprehensive drug screening was conducted for all samples using ultra-high-performance liquid chromatography-high-resolution mass spectrometry. A total of 71 blood and urine and 50 hair samples were analyzed to confirm the suitability of the ultra-high-performance liquid chromatography-high-resolution mass spectrometry method for the study purposes. The main substances found in blood and urine were antipsychotics (71.8% and 66.2%) and benzodiazepines (62.0% and 59.2%), respectively, whereas cocaine (84.0%) and antipsychotics (74.0%) was more evident in hair. Z-drugs were detected in blood (7.0%), urine (5.6%), and hair (24%) samples; amphetamines were mainly detected in hair samples (14.0%). Synthetic cathinones were the most frequently detected NPS in hair specimens (8.0%), whereas synthetic cannabinoids were mainly found in blood samples (11.3%). These analyses showed that patients were polydrug users (77.5% detected in blood and urine, and 94.0% in hair). Comprehensive screening enabled the assessment of past, recent, and actual consumption of psychoactive substances, including licit and illicit drugs and NPS, by psychiatric patients. A thorough understanding of substance consumption patterns can enhance therapeutic interventions and management of psychiatric disorders associated with psychoactive substance use.